Improving library services through digital-based promotion - Eny Supriati; Hari Murbayanto (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
Libraries use learning resources and information providers that have an essential role in increasing their promotion through digital. The IAIN Ponorogo library is one of the libraries that has implemented several digital-based library promotions. This research is to determine how to implement digital-based library promotions and understand the obstacles in carrying out activities through social media. The method uses a qualitative approach with the type of case study. They are collecting data through participatory observation and interviews. The data analysis technique uses Miles and Huberman's interactive design, which includes data reduction, data presentations, and conclusion drawings. The results show that efforts to improve services through digital promotions at the IAIN Ponorogo library have developed quite well. There are several digital-based promotional models, namely: library branding with the CERIA (Intelligent, Effective and Efficient, Friendly, Sincere, and Trustworthy), library copywriting, library websites, library vlogs, and the application of library social media (Instagram, Facebook, WhatsApp (chat only)). The problem is that there are no program designs, individual budgets for promotion development, and professionals in the field of information technology.